Physical Inactivity and Related Barriers: A Study in a Community Dwelling of Older Brazilians - Sebastião Gobbi; Emerson Sebastião; Camila Bosquiero Papini; Priscila Missaki Nakamura; Américo Valdanha Netto; Lilian Teresa Bucken Gobbi; Eduardo Kokubun (Journal of Aging Research)
This study sought to investigate the prevalence of physical inactivity and related barriers in older Brazilian adults. A cross-sectional, population-based study was conducted, and a stratified random sampling procedure was used. A total of 359 older adults were interviewed. The long version of the International Physical Activity Questionnaire (IPAQ) and the Questionnaire of Barriers to Physical Activity Practice were used to assess physical activity level and barriers, respectively. No statistically significant difference was observed on the prevalence of physical inactivity in either gender or age groups. Regarding barriers, the proportion of 9 out of 22 barriers was statistically significant between men and women. Self-reported physical inactivity/activity in older Brazilian adults continues to be a concern. Uncommonly, older males reported a higher prevalence of physical inactivity compared to their counterparts. Additionally, physical inactivity prevalence continued to increase with the aging process. Yet, personal barriers such as lack of time and poor health were strongly associated with physical inactivity. The results of this study may help health professionals and public policy makers to better address the issues related to a healthy lifestyle among older adults and promote physical activity among Brazilian older adults and in other countries with similar characteristics.